Answer:
c. f(x) x+1/x-1
Step-by-step explanation:
To answer this question, we need to check each answer one by one until we find the right one.
y = (x+6)/(x-6)
switch x and y
x = (y+6)/(y-6)
solve for y
x(y-6) = y+6
xy - 6x = y+6
y(x-1) = 6x+6
y = (6x+6) /(x-1) = 6(x+1)/(x-1)
f^-1(x) = 6(x+1)/(x-1)
y = (x+2)/(x-2)
switch x and y
x = (y+2)/(y-2)
solve for y
x(y-2) = y+2
xy -2x = y+2
y(x-1) = 2x+2
y = (2x+2)/(x-1)
f^-1(x) = 2(x+1)/(x-1)
y = (x+1)/(x-1) ------ correct one
switch x and y
x = (y+1)/(y-1)
solve for y
x(y-1) = y+1
xy - x = y+1
y(x-1) = x+1
y = (x+1)/(x-1)
f^-1(x) = (x+1)/(x-1)
f(x) = f^-1(x)
Answer:
44.159
Step-by-step explanation:
Answer:
Step-by-step explanation:
Let's do this properly:
Area of trapezoid = average length times height.
Here,
Area = (1/2)(8 cm + 14 cm)(8 cm), or
= (11 cm)(8 cm) = 88 cm^2
It appears that Tina forgot to divide the sum of 14 cm and 8 cm by 2. Thus, her answer is twice as large as it should be.